The role of human will in love from the perspective of verses, hadiths and thinkers - ensieh kashani; mohammad rokkai; mehdi nosratian (اخلاق وحیانی, 2021)
The importance of the subject of love in Islamic anthropology has caused scientists to discuss it in detail or briefly, despite the fact that this issue has long been widely considered by scientists, but the role of the human will in love has not been much considered ‌اند. But the voluntary nature of love in the Qur'an and Hadith is proven by evidence. One of these evidences is the use of the substance of love in the Qur'an.This chapter has a kind of cause because it adds the meaning of seeking to the meaning of the root of the verbThe meaning of preference is created in the meaning of love. Also, verses and hadiths that name negative and negative loves recognize the existence of a kind of authority in human love. Another evidence in the acceptance of the human will in love by verses and hadiths is that love can be guided from the perspective of verses and hadiths.